2007
DOI: 10.1128/iai.01435-06
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fatty Acids and Cholesterol Present in Bile on Expression of Virulence Factors and Motility of Vibrio cholerae

Abstract: Bile induces pleiotropic responses that affect production of virulence factors, motility, and other phenotypes in the enteric pathogen Vibrio cholerae. Since bile is a heterogeneous mixture, crude bile was fractionated, and the components that mediate virulence gene repression and enhancement of motility were identified by nuclear magnetic resonance, gas chromatography (GC), and GC-mass spectrometry analyses. The unsaturated fatty acids detected in bile, arachidonic, linoleic, and oleic acids, drastically repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
136
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(145 citation statements)
references
References 29 publications
2
136
1
5
Order By: Relevance
“…Further studies are required to fully understand how V. cholerae integrates these host signals. Intriguingly, fatty acids present in bile negatively regulate virulence gene expression (9), indicative of fine-tuned negative feedback of virulence gene regulation, further illuminating the complexity of the host-pathogen interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies are required to fully understand how V. cholerae integrates these host signals. Intriguingly, fatty acids present in bile negatively regulate virulence gene expression (9), indicative of fine-tuned negative feedback of virulence gene regulation, further illuminating the complexity of the host-pathogen interaction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that certain environmental conditions such as temperature, oxygen concentration, osmolarity, pH, and iron availability (4-6) influence expression of virulence genes in vitro. In addition, bicarbonate and fatty acids, which are abundant in host small intestines, modulate virulence gene expression through ToxT (7)(8)(9). Intriguingly, different in vitro conditions are required to activate virulence genes in different biotypes of V. cholerae.…”
mentioning
confidence: 99%
“…cholerae primarily inhabits aquatic environments and causes the human disease known as cholera (290). Virulent serogroups of V. cholerae form robust biofilms and express the virulence factors cholera toxin (CT) and the toxin-coregulated pilus (TCP) (290,291). The maturation and dispersal of V. cholerae biofilms, as well as the production of CT and TCP, are controlled by multiple independent quorum-sensing systems, whose effects converge on a single regulatory circuit (Fig.…”
Section: Vibrio Choleraementioning
confidence: 99%
“…These findings suggest that FFAs act by blocking the activity of PrfA, possibly by generating an inhibitory signaling event via the membrane, or by direct binding to the PrfA protein itself [4]. Interestingly, unsaturated long-chain FFAs present in bile are known to inhibit the expression of two primary virulence genes in Vibrio cholera, encoding the cholera toxin and toxin-coregulated pilus [11]. The transcription factor ToxT, belonging to the AraC family, directly activates expression of cholera toxin and toxin-coregulated pilus, but the presence of unsaturated long-chain FFAs inhibits ToxT-dependent activation.…”
Section: How Do Naturally Occurring Free Fatty Acids Sabotage Listerimentioning
confidence: 99%